1992
DOI: 10.1136/gut.33.12.1590
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal motor function before and after healing of oesophagitis.

Abstract: Forty three patients with reflux oesophagitis were studied to investigate the effect of healing on oesophageal function. All patients underwent oesophageal manometry and transit studies before and after complete healing of oesophagitis. Oesophagitis was treated with omeprazole 40 mg/day for a median duration of 12 weeks. Twenty three patients also had an acid clearance test before and after healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 16 publications
4
44
1
1
Order By: Relevance
“…However, relapse is almost the rule in children with GORD after repaired oesophageal atresia or GORDassociated with connective tissue disorders and neurological disease [37]. In these children, oesophageal motor abnormalities persist after healing of the oesophagitis [36] and resemble that in adults [46,60,112,113,115,120].…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, relapse is almost the rule in children with GORD after repaired oesophageal atresia or GORDassociated with connective tissue disorders and neurological disease [37]. In these children, oesophageal motor abnormalities persist after healing of the oesophagitis [36] and resemble that in adults [46,60,112,113,115,120].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Currently, the most reliable data is that the abnormalities of oesophageal motor function in patients with reflux oesophagitis do not improve after complete healing of oesophagitis (Singh et al,1992). This suggests that oesophageal dysmotility is a primary phenomenon and not a consequence of injury and inflammation.…”
Section: Wwwintechopencommentioning
confidence: 95%
“…Gill et al have reported shorter durations of contraction in this condition (Gill et al,1986). On the other hand, Singh et al have found a longer durations of contraction in patients with GERD compared with the controls (Singh et al,1992). Oesophageal transit and acid clearance have also been shown to be slower in these patients (Singh et al,1992).…”
Section: Wwwintechopencommentioning
confidence: 97%
See 2 more Smart Citations